2014
DOI: 10.1038/ncomms6291
|View full text |Cite
|
Sign up to set email alerts
|

Graphenes in the absence of metals as carbocatalysts for selective acetylene hydrogenation and alkene hydrogenation

Abstract: Catalysis makes possible a chemical reaction by increasing the transformation rate. Hydrogenation of carbon-carbon multiple bonds is one of the most important examples of catalytic reactions. Currently, this type of reaction is carried out in petrochemistry at very large scale, using noble metals such as platinum and palladium or first row transition metals such as nickel. Catalysis is dominated by metals and in many cases by precious ones. Here we report that graphene (a single layer of one-atom-thick carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
197
0
8

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 222 publications
(212 citation statements)
references
References 51 publications
(48 reference statements)
6
197
0
8
Order By: Relevance
“…[4][5][6][7][8] It was recently reported that graphenes can be carbocatalysts to promote hydrogenation of carbon-carbon multiple bonds. [9,10] Purposely addition of metal at the ppm level has provided evidence supporting the theory that metal impurities present on graphene do not play a significant role in the process at the low percentages generally found in graphenes. Considering that hydrogenation is one of the most general organic reactions, widely used in organic synthesis and chemical industry, it is of interest to expand the initial results on the catalytic activity of graphene to the hydrogenation of other functional groups in addition to carbon-carbon multiple bonds, such as nitro groups.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…[4][5][6][7][8] It was recently reported that graphenes can be carbocatalysts to promote hydrogenation of carbon-carbon multiple bonds. [9,10] Purposely addition of metal at the ppm level has provided evidence supporting the theory that metal impurities present on graphene do not play a significant role in the process at the low percentages generally found in graphenes. Considering that hydrogenation is one of the most general organic reactions, widely used in organic synthesis and chemical industry, it is of interest to expand the initial results on the catalytic activity of graphene to the hydrogenation of other functional groups in addition to carbon-carbon multiple bonds, such as nitro groups.…”
mentioning
confidence: 82%
“…As activation of hydrazine is believed to occur through hydrazine oxidation to diimine followed by spontaneous diimine decomposition to nitrogen, [21][22][23] the types of sites promoting this nitro group reduction in CNTs using hydrazine should be expected to be, in principle, oxidation sites and, therefore, different types of sites from those required for hydrogen activation. [10] In other words, a material could promote reduction by hydrazine and be inactive for activation of hydrogen gas, as it has been reported for instance for MIL-53(Al), a metal organic framework able to activate hydrazine for multiple carbon-carbon bond reduction. [24] Thus, the outcome of the present study cannot be directly predicted from the results reported so far with CNTs as hydrazine hydrogenation promoter, activation of molecular hydrogen being more challenging owing to the strength of the HÀH bond and of more general applicability.…”
mentioning
confidence: 96%
See 3 more Smart Citations